2021
DOI: 10.1002/1878-0261.13101
|View full text |Cite
|
Sign up to set email alerts
|

The epithelial splicing regulator ESRP2 is epigenetically repressed by DNA hypermethylation in Wilms tumour and acts as a tumour suppressor

Abstract: Wilms tumour (WT), an embryonal kidney cancer, has been extensively characterised for genetic and epigenetic alterations, but a proportion of WTs still lack identifiable abnormalities. To uncover DNA methylation changes critical for WT pathogenesis, we compared the epigenome of foetal kidney with two WT cell lines, filtering our results to remove common cancer‐associated epigenetic changes and to enrich for genes involved in early kidney development. This identified four hypermethylated genes, of which ESRP2 (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Although in this study we did not perform functional validation, the putative splicing regulators that we identified here (ESRP1, ESRP2, RBFOX2, and QKI) were found to have similar functionality in other developing organs and in-vitro systems 10 , 28 , 30 , 31 , 35 , 37 , 49 , as well as in the kidney. For example, a recent study showed that the splicing regulator ESRP2 is repressed in Wilms’ tumors by DNA methylation from their very early stages (nephrogenic rests) 50 , and that over-expression of ESRP2 in Wilms’ tumor cell lines inhibits their proliferation both in-vitro and in-vivo . Another study showed that Esrp1 ablation in mice, alone or together with Esrp2, results in reduced kidney size, fewer ureteric tips, reduced nephron numbers, and a global reduction of epithelial splice isoforms in the transcriptome of ureteric epithelial cells 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Although in this study we did not perform functional validation, the putative splicing regulators that we identified here (ESRP1, ESRP2, RBFOX2, and QKI) were found to have similar functionality in other developing organs and in-vitro systems 10 , 28 , 30 , 31 , 35 , 37 , 49 , as well as in the kidney. For example, a recent study showed that the splicing regulator ESRP2 is repressed in Wilms’ tumors by DNA methylation from their very early stages (nephrogenic rests) 50 , and that over-expression of ESRP2 in Wilms’ tumor cell lines inhibits their proliferation both in-vitro and in-vivo . Another study showed that Esrp1 ablation in mice, alone or together with Esrp2, results in reduced kidney size, fewer ureteric tips, reduced nephron numbers, and a global reduction of epithelial splice isoforms in the transcriptome of ureteric epithelial cells 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The RNA binding protein epithelial splicing regulatory protein 1 (ESRP1), for example, has been shown to regulate the splicing of CD44, and knockdown of ESRP1 was shown to suppress lung cancer metastasis [38]. Specifically in Wilms' tumor, a recent study showed that the splicing regulator ESRP2 is repressed by DNA methylation, whereas the overexpression of ESRP2 in Wilms' tumor cell lines promotes alternative splicing and inhibits cell proliferation both in vitro and in vivo [39].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, RNA binding proteins known to regulate mRNA splicing were found to be abnormally expressed or somatically mutated in cancer [29][30][31][32][33]. Specifically in Wilms' tumor, a recent study showed that the splicing regulator ESRP2 is repressed by DNA methylation, whereas over-expression of ESRP2 in Wilms' tumor cell lines promotes alternative splicing and inhibits cell proliferation both in-vitro and in-vivo [34]. In a recent work, we also found that fetal kidney cells at an early developmental stage have a mesenchymal splice-isoform profile that is similar to that of blastemal-predominant Wilms' tumor xenografts [35].…”
Section: Introductionmentioning
confidence: 99%